Relation between left ventricular filling pressure and angiographic findings in coronary heart disease. Ventriculography used as a stress test. Issue 1 (January 1977) - Forfang, K; Andersen, A; Simonsen, S; Stake, G
Abstract : In 80 male patients with coronary heart disease maximum diastolic pressure in the left ventricle (LVMDP) (usually the top of the a wave), and 'post a' end-diastolic pressure (LVEDP) before and 2 and 3 minutes after ventriculography were correlated to angiographic estimates of left ventricular function (aneurysm, ejection fraction (EF), and to lesions shown by selective coronary arteriography using a score system (coronary artery lesions index, CALI). A significant correlation between CALI and LVEDP (or LVMDP) could not be shown either before or after ventriculography. Before ventriculography, however, LVEDP and LVMDP were good predictors of left ventricular dyskinesia (aneurysm and/or EF less than 50%). A positive and significant correlation between CALI and the LVEDP (and LVMDP) increments following ventriculography (delta LVEDP, delta LVMDP) was found in patients with LVEDP (or LVMDP) below 12 mmHg before ventriculography. Using delta LVEDP the correlation coefficient was 0-51 (n = 41, P less than 0-001, 95 per cent confidence interval 0-24 to 0-88). Using delta LVMDP r = 0-47 (n = 41, 0-001 less than P less than 0-01). Delta LVEDP greater than 12 mmHg was found only in patients with triple vessel disease.